2010
DOI: 10.1007/bf03326193
|View full text |Cite
|
Sign up to set email alerts
|

Institutional scale operational symbiosis of photovoltaic and cogeneration energy systems

Abstract: Due to the negative environmental effects of fossil fuel combustion, there is a growing interest in both improved efficiency in energy management and a large-scale transition to renewable energy systems. Using both of these strategies, a large institutional-scale hybrid energy system is proposed here, which incorporates both solar photovoltaic energy conversion to supply renewable energy and cogeneration to improve efficiency. In this case, the photovoltaic reduces the run time for the cogeneration to meet loa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…Since it is considered clean and sustainable to transform solar energy directly to electricity, many countries have announced that photovoltaic energy is going to play an essential role in electricity generation in the near future. EPIA (2009); Karbassi et al (2010); Mostofi et al (2011) estimated that overall annual installation of photovoltaic systems will increase by more than three times by 2013. In fact, overall installation has grown 15 times from 1998 to 2008.…”
Section: Introductionmentioning
confidence: 99%
“…Since it is considered clean and sustainable to transform solar energy directly to electricity, many countries have announced that photovoltaic energy is going to play an essential role in electricity generation in the near future. EPIA (2009); Karbassi et al (2010); Mostofi et al (2011) estimated that overall annual installation of photovoltaic systems will increase by more than three times by 2013. In fact, overall installation has grown 15 times from 1998 to 2008.…”
Section: Introductionmentioning
confidence: 99%
“…Simultaneous generation of different energy forms (i.e. electric and heat) in one combined production system enables efficiency in fuel use; since conventional electric energy producing systems "waste" the produced heat (Mostofi et al 2011). Less fuel is required to generate the same amount of energy compared to conventional systems (Afgan and Darwish 2011).…”
Section: Introductionmentioning
confidence: 99%
“…For residential-scale photovoltaic arrays, the development of small-scale combined heating and power (CHP) systems has provided the opportunity for in-house power backup [33]. Recent work has shown that small-scale CHP and PV technologies can produce significant emission reductions at the residential level [34,35]. Other hybrid systems include PV-Diesel [36,37], PV-Wind [38][39][40], or PV-Wind-Diesel systems [41][42][43][44].…”
Section: Introductionmentioning
confidence: 99%